Melanotic oncocytic metaplasia of the nasopharynx as a benign mimicker of malignant melanoma: a case report - Oka Shiori; Mori Kiyoshi; Kondo Takeshi; Morinaka Setsuko (BMC, 2010)
Abstract Introduction Melanotic variant of oncocytic metaplasia of the nasopharynx is an extremely rare condition. Case report A 73-year-old Japanese man presented with nasal congestion and chill. Nasoscopic examination revealed multiple black nodules around the bilateral torus tubarius. The nodules were biopsied to determine the histology. The clinical differential diagnosis was malignant melanoma or hemangioma. Microscopically, there were oncocytic plump cells with abundant brown pigmented granules showing glandular pattern. No significant atypia was found. The pigment was positive for Fontana-Masson staining, and negative for Berlin blue staining, showing that it was melanin pigment. Immunohistochemically, S100-positive HMB45-negative dendritic cells were also found. Conclusion Such a pigmented variant of benign oncocytic lesion is very rare, and only 15 cases have been reported in the English literature. As a benign mimicker of malignant melanoma, melanocytic oncocytic metaplasia should be always taken into consideration in the clinical setting.